Expert Answers
embizze eNotes educator| Certified Educator

Solve ln(ln(ln(ln(x))))=0:

ln(ln(ln(ln(x))))=0 ==> ln(ln(ln(x)))=1 since ln(a)=0 ==>a=1; here a=ln(ln(ln(x)))

Now ln(ln(ln(x)))=1==>ln(ln(x))=e since ln(a)=1 ==>a=e

Then `ln(x)=e^e`

And finally `x=e^(e^e)`







` `


jeew-m eNotes educator| Certified Educator

In logarithm we know that if;

lnx = y then;

`x = e^y`


In the same manner;

`ln(ln(ln(lnx))) = 0`

`(ln(ln(lnx))) = e^0 = 1`

`(ln(lnx)) = e^1 = e1`

`lnx = e^(e1)`

`x = e^(e^(e1))`


So the answer is  `x = e^(e^(e1))`

Access hundreds of thousands of answers with a free trial.

Start Free Trial
Ask a Question